FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA KAFE FIVE POINTS SEMARANG - Akbar, Masfufah Hanik; Ferdinand, Augusty Tae (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to explain the influence of product quality and service quality in influencing customer value, in order to influence purchasing decision which customer value is used as an intervening variable between product quality and service quality to purchasing decision in Five Points Cafe at Semarang. This research was conducted by taking samples using purposive sampling technique, those are consumers who have visited and bought Five Points product. The collection of data obtained from 100 customers Five Points by giving questionnaires which consist of open and closed questions. Respondents' answers to open-ended questions were analyzed qualitatively, and answers to the closed questions were analyzed by Multiple Linear Regression using SPSS program. The result show that product quality and service quality has positive and significant impact on customer value with the regression value of 0.582 and 0.282, and the customer value has a positive and significant effect to purchasing decision with regression value of 0.391. Brand image has a positive impact not significant to Purchasing decision with the regression value of 0.150. First structure shown that 58.7% customer value variable can be explained by product quality and service quality variable. While the second structure shown that 24.1% purchasing decision can be explained by customer value and brand image. And for the rest can be explained by other variables that beyond research.